2019
DOI: 10.1101/850677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computing Skin Cutaneous Melanoma Outcome from the HLA-alleles and Clinical Characteristics

Abstract: AbstractHuman Leukocyte Antigen (HLA) is an essential component of the immune system which stimulates immune cells to provide protection and defense against cancer. More than thousands of HLA alleles have been reported in the literature; but, only a specific set of HLA alleles expressed in an individual. Recognition of cancer-associated mutations by the immune system depends on the presence of a particular set of alleles, that elicit an immune response to fight against cancer. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In one of our previous studies [ 59 ], Human Leukocyte Antigen (HLA) alleles-based features were used in combination with clinical information, for the prognostication of melanoma patients. The study used a dataset of 401 patients for developing ML based models.…”
Section: Resultsmentioning
confidence: 99%
“…In one of our previous studies [ 59 ], Human Leukocyte Antigen (HLA) alleles-based features were used in combination with clinical information, for the prognostication of melanoma patients. The study used a dataset of 401 patients for developing ML based models.…”
Section: Resultsmentioning
confidence: 99%
“…HLA-DPB1 is derived from the β chain of HLA-II. In a previous research, Dhall et al [ 25 ] showed that HLA-DPB1 functioned in presenting abnormal antigens in MM, thus stimulating melanoma progression and metastasis. In gene polymorphism research, HLA-DPB1 mutations have been regarded as signatures associated with gastric and lung cancers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…12, 29 In present study, to evaluate the developed machine learning models, we have applied 5-fold cross-validation on 80% of the training data for the internal training, testing and model evaluation. 30, 31 In 5-fold CV, the training data is divided into 5-sets, where four sets were used for the training and fifth set was utilized for the testing purposes. The same process is repeated five times, so that each set of positive and negative data is used for training and testing purposes.…”
Section: Methodsmentioning
confidence: 99%